Memory T Cell Migration - Zhang, Qianqian; Lakkis, Fadi G. (Frontiers in Immunology, 2015)
Immunological memory is a key feature of adaptive immunity. It provides the organism with long-lived and robust protection against infection. In organ transplantation, memory T cells pose a significant threat by causing allograft rejection that is generally resistant to immunosuppressive therapy. Therefore, a more thorough understanding of memory T cell biology is needed to improve the survival of transplanted organs without compromising the host’s ability to fight infections. This review will focus on the mechanisms by which memory T cells migrate to the site where their target antigen is present, with particular emphasis on their migration to transplanted organs. First, we will define the known subsets of memory T cells (central, effector, and tissue resident) and their circulation patterns. Second, we will review the cellular and molecular mechanisms by which memory T cells migrate to inflamed and non-inflamed tissues and highlight the emerging paradigm of antigen-driven, trans-endothelial migration. Third, we will discuss the relevance of this knowledge to organ transplantation and to the prevention or treatment of allograft rejection.